LEARNING, MEMORY AND EMOTION: A SYSTEMATIC REVIEW (CIPEEX, 2022)
MEMORY IS THE COGNITIVE PROCESS THAT INCLUDES, CONSOLIDATES AND RECOVERS ALL THE INFORMATION WE LEARN, THE FORMATION OF ALL MEMORIES REQUIRES MORPHOLOGICAL CHANGES IN THE SYNAPSES: NEW SYNAPSES MUST BE FORMED AND OLD ONES MUST BE STRENGTHENED. EMOTION IS THE REACTION CAPACITY, USUALLY BRIEF AND INTENSE, RELATED TO A SPECIFIC ENVIRONMENTAL EVENT. THIS WORK AIMED TO CORRELATE EMOTION, MEMORY AND ITS EFFECTS ON LEARNING, ADDRESSING THE BRAIN AREAS AND THE SUBSTANCES INVOLVED. THE ARTICLES "MEMORY", "EMOTION", "LEARNING" AND "MOOD" WERE SEARCHED ON PLATFORMS SUCH AS PUBMED AND SCIELO, AND 5 ARTICLES PUBLISHED BETWEEN 2004 AND 2018 WERE SELECTED FOR REVIEW. THE LITERATURE DEMONSTRATES THAT THE CORRELATION BETWEEN MEMORY, HUMOR, AND LEARNING IS UNDENIABLE, AND THAT THE AMYGDALA, HIPPOCAMPUS, AND CORTICES ARE THE MAJOR WORKING BRAIN CENTERS.
Keywords: Memory, emotion, cognition, brain areas.